Peyronie's Disease: Literature Review of Peyronies’s Disease Management: Peyronie Disease: Tinjauan Literatur Manajemen Peyronie Disease - Muhammad Irfan Hamdi (Jurnal Medika Hutama, 2024)
Peyronie's disease is a sexual disease or medical disorder where the clinical manifestation is penile deformity in the form of penile curvature that occurs in 0.5-20.3% of the male population and is characterized by fibrotic plaques in the tunica albuginea. Aim: To provide information obtained from the literature review process. Methods: Literature search using the keyword 'Peyronie's disease and treatment' in PubMed. Result: